Osteoarticular involvement in childhood brucellosis: evaluation of clinical, laboratory and radiologic features of 185 cases - AKKOÇ, GÜLŞEN (My University, 2023)
Backgrounds: Brucellosis is a systemic zoonotic disease. Osteoarticular (OA) system involvement is a common complication and the predominant manifestation of brucellosis in children. We aimed to evaluate the epidemiologic, demographic, clinical characteristics, and laboratory and radiologic findings of children with brucellosis and how these related to OA involvement. Methods: This retrospective cohort study consisted of all consecutive children and adolescents diagnosed as having brucellosis who were admitted to the pediatric infectious disease department of University of Health Sciences Van Research and Training Hospital between August 1, 2017, and December 31, 2018, in Turkey. Results: A total of 185 patients diagnosed as having brucellosis were evaluated, 50.8% had OA involvement (n = 94). Seventy-two patients (76.6%) exhibited peripheral arthritis involvement, among of them, hip arthritis (63.9%; n = 46) was the most common manifestation, followed by arthritis of knee (30.6%; n = 22), shoulder (4.2%; n = 3) and elbow (4.2%; n = 3). A total of 31 patients (33.0%) had sacroiliac joint involvement. Seven patients (7.4%) had spinal brucellosis. Erythrocyte sedimentation rate level above 20 mm/h at admission and age were independent predictor of OA involvement (respectively odds ratio [OR] = 2.82; 95% confidential interval [CI] = 1.41-5.64, ORperyear= 1.10; 95% CI: 1.01-1.19). Increasing age was associated types of OA involvement. Conclusion: A half of brucellosis cases had OA involvement. These results can help physicians to make early identification and diagnosis of childhood OA brucellosis who present with arthritis and arthralgia to enable the disease to be treated in time.
Keywords: Tıp; Mikrobiyoloji ve Klinik Mikrobiyoloji; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Microbiology and Clinical Microbiology; Internal Medicine Sciences; Child Health and Diseases; Life Sciences; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; Mikrobiyoloji; PEDİATRİ; BULAŞICI HASTALIKLAR; MİKROBİYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; MICROBIOLOGY; PEDIATRICS; INFECTIOUS DISEASES; Pediatri, Perinatoloji ve Çocuk Sağlığı; Mikrobiyoloji (tıbbi); Bulaşıcı hastalıklar; Pediatrics, Perinatology and Child Health; Microbiology (medical); Infectious Diseases; Arthritis, Brucellosis; children; osteoarticular involvement; radiology; Arthritis; Brucellosis; children; osteoarticular involvement; radiology